(untitled) (Academicia Globe: Inderscience Research, 2021)
The verb is a part of speech which denotes an action. The verb has the following grammatical categories: person, number, tense, aspect, voice and mood. These categories can be expressed by means of affixes, inner flexion (change of the root vowel) and by form words. Verbs may be transitive and intransitive.